Pengaruh Keselamatan Kerja Terhadap Kinerja Karyawan Pada PT. PLN (Persero) Unit Induk Pembangunan II Medan - Lukman Nasution; Reza Nurul Ichsan (Mahesa Research Center, 2020)
This study aims to determine the magnitude of the effect of occupational safety on employee performance on PT. PLN (Persero) Unit Induk Pembangunan II Medan, This study was conducted on the scope of PT. PLN (Persero) Unit Induk Pembangunan II Medan. Samples were taken as many as 30 Respondents and the analytical method used is simple linear regression analysis where the constant is 6,541 which means that if constant variable then the level of employee performance variable is positive value that is equal to 0,771 which means if work safety have increase by 1 percent hence employee performance will experience increase equal to 0,771, second These variables have a positive attachment relationship to employee performance and have significant value is 0.000 <from 0.005. Result of t test analysis yield t value is equal to 7,366 bigger than tTabel value equal to 2,763, meaning work safety variable have significant effect to employee performance.